The European Single Market at 25 - Elisabeth Bublitz (Intereconomics, 2018)
This year we celebrate the 25th anniversary of the European Single Market. The Single Market's achievements cover various areas but there is still room for improvement. Against the background of this historic and economic development, this article discusses different legal acts that are being negotiated and outlines suggestions for improvement.
Keywords: 330; Single European Market; EU budget; EU countries; European integration